The Role of Political Institutions in Africa In Building Democratic Governments - Idris Mahmoud Idris; Elfatih Abdullahi Abdelsalam; Abdulhamid Mohamed Ali Zaroum (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
Abstract The “third wave” of democratization, which saw the fall of old authoritarian regimes across Africa, as well as the introduction of multiparty elections and other significant new changes, has faded. Today, we are witnessing a reversal of democratic gains in favour of dictatorship, resulting in political instability and severe outbreaks of violence in Ethiopia, Mozambique, Kenya, the Ivory Coast, Nigeria, and elsewhere. This article seeks explanation for the failures of the democratization process in Africa, focusing on the challenging role of political institutions in determining the nature of transition trajectories, reviewing its significance, and justifying why this factor is important when analyzing the success or failure of democratization. The paper sought to provide a more robust understanding of Africa’s democratization failure and the thorny issue of a transitional path toward good governance. The study found that the progress of the democratic transition process at any given point in history is dependent on the existence of powerful and capable political institutions equipped to face and respond to the challenges of the transition process, and that the more integrated and independent government and civil society institutions are, the more likely democratic practices will thrive. Furthermore, the study showed that under authoritarianism, institutions like elections, political parties, and legislatures are often referred to as "pseudo-democratic" because they are copied, imitated, and mocked to manipulate the concept of democracy and serve the continuation of autocratic rule. Keywords: Democratization; Africa; Political Institutions; Authoritarianism.